The Iraqi- Kuwaiti Dispute and the U.S. Attempts to Exploit it 1990-1991 - Ali Shabeeb Al- Mohammady, Hamid Abed (Journal of Tikrit University for Humanities, 2023)
The research sheds light on the size of the military capacity which Iraq got after its war with Iran, which constituted a source of concern and a threat to the balance of power controlled by Israel in the Middle East. It also shows how the Zionist organizations were working to influence the American administration to force it to confront this danger. The American administration exploited the Iraqi dispute with Kuwait, and then gave Iraq the green light to attack, and to begin the stage of revenge against it and thus destroy its military capabilities that threaten American interests in the region.